KAJIAN JENIS KEMASAN DAN LAMA PENYIMPANAN TERHADAP MUTU ES KRIM SOYGHURT - Rinaldi Satria; Evy Rossi; Noviar Harun (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2017)
The aimed of the research to evaluate the influence of packaging type and time storage on ice cream soyghurt quality. This study used Completely Randomized Design with 2 factor treatments, packaging type (polipropilen and composite paper) and time storage (0 day, 1 week, 2 weeks, 3 weeks, 4 weeks) followed by DNMRT test at 5%. The treatment in this study were K1T0 (polypropylene packing on 0 day storage), K1T1 ( polypropylene at 1 week storage), K1T2 (polypropylene at 2 weeks storage), K1T3 (polypropylene at 3 weeks storage), K1T4 (polypropylene on 4 weeks storage), and K2T0 (composite paper on 0 day storage), K2T1 (composite paper on 1 week storage), K2T2 (composite paper at 2 weeks storage), K2T3 (composite paper at 3 weeks storage), K2T4 (Composite paper at 4 weeks storage). Test results up to 4 weeks of soyghurt ice cream still comply with Indonesian National Ice Cream Standards. Soyghurt ice cream stored up to 4 weeks using polypropylene packaging is better than composite paper packaging with 19.18% fat content, total lactic acid bacteria 9.73 CFU/ml, acidity (pH) 4.61, melting time 22.63 minutes and overrun 29.64%. Key words : ice cream, soyghurt, packing type, storage time